Schizotypal personality traits and problematic use of massively-multiplayer online role-playing games (MMORPGs). (September 2017) - Schimmenti, Adriano; Infanti, Alexandre; Badoud, Deborah; Laloyaux, Julien; Billieux, Joël
Abstract: A link between maladaptive personality traits and an excessive use of massively multiplayer online role-playing games (MMORPGs) has been documented. However, the role of schizotypal personality traits in MMORPG use is understudied. The aim of this study was to explore the potential links between schizotypal traits, motivations for playing MMORPGs, and symptoms of problematic MMORPG use. Eighty-three MMORPG gamers were enrolled in the study. They filled out questionnaires measuring schizotypal personality traits and an adapted version of the same scale designed to measure in-game schizotypal traits. All participants also filled out questionnaires assessing motivations for gaming and disordered use of MMORPGs. Results of the study showed that the disorganized and interpersonal traits of schizotypy decreased when participants were thinking about themselves in the virtual world. Schizotypal traits, together with achievement and immersion motives, predicted problematic use of MMORPGs. The findings of this study may suggest that schizotypal traits and motivations for playing can interact and play a pivotal role in the onset and maintenance of problematic gaming. Highlights: Eighty-three MMORPG players participated in the study. In-game versus real-life schizotypal traits were assessed. Self-reported schizotypal traits were less elevated in game than in real life. Schizotypy and gaming motives (immersion and achievement) predicted problem gaming.